SAVINGS AND LOANS APPLICATIONS IN DEVELOPING TEACHER COOPERATION SUB CIBITUNG (TCSC) USING VISUAL FOXPRO 5.0 - Sri Nuraeni; Linda Wahyu Widianti, SKom, MMSI Linda Wahyu Widianti, SKom, MMSI (Jurnal Sistem Informasi, 2007)
The application of this program will eventually include about credit paymentinformation each time that the transaction can be more easily and to optimize thesupervision of each month. With the help of supporting applications created withVisual FoxPro 5.0 is expected to ease in knowing the members and their paymentinformation will ease the credit and cooperatives minister reporting.